Expulsion and extradition as means of strengthening criminal law in Brazil from Empire to Republic*: *Article not peer-reviewed (Italian Review of Legal History, 2020)
The work aims to reconstruct the legal regulation of expulsion and extradition in Brazil between the 19th and 20th century in order to demonstrate those instruments of international law were were used as means of strengthening the criminal law. For this, an analysis of Brazilian legislation and legal scholarship was carried out during the empire and republic and has used the Italo-Brazilian treaties and Italian sources. It is noted that the provisions have presented a framework of progressive mitigation of protection and have served as an anchor to a expansive ultrastate criminal law.
Keywords: Extradition; Expulsion; Citizenship; Brazil (XIX-XX century); Criminal Law